The atypical β‐blocker S‐oxprenolol reduces cachexia and improves survival in a rat cancer cachexia model. Issue 1 (8th November 2022) - Yuan, Luping; Springer, Jochen; Palus, Sandra; Busquets, Silvia; Jové, Queralt; Alves de Lima Junior, Edson; Anker, Markus S.; von Haehling, Stephan; Álvarez Ladrón, Natalia; Millman, Oliver; Oosterlee, Annemijn; Szymczyk, Agata; et al.
Abstract: Background: Beta‐blockers and selected stereoisomers of beta‐blockers, like bisoprolol and S‐pindolol (ACM‐001), have been shown to be effective in preclinical cancer cachexia models. Here, we tested the efficacy of stereoisomers of oxprenolol in two preclinical models of cancer cachexia—the Yoshida AH‐130 rat model and the Lewis lung carcinoma (LLC) mouse model. Methods and Results: In the Yoshida AH130 hepatoma rat cancer cachexia model and compared with placebo, 50 mg/kg/d S‐oxprenolol (HR: 0.49, 95% CI: 0.28–0.85, P = 0.012) was superior to 50 mg/kg/d R‐oxprenolol (HR: 0.83, 95% CI 0.38–1.45, P = 0.51) in reducing mortality (= reaching ethical endpoints). Combination of the three doses (12.5, 25 and 50 mg/kg/d) that had a significant effect on body weight loss in the S‐oxprenolol groups vs the same combination of the R‐oxprenolol groups lead to a significantly improved survival of S‐oxprenolol vs R‐oxprenolol (HR: 1.61, 95% CI: 1.08–2.39, P = 0.0185). Interestingly, there is a clear dose dependency in S‐oxprenolol‐treated (5, 12.5, 25 and 50 mg/kg/d) groups, which was not observed in groups treated with R‐oxprenolol. A dose‐dependent attenuation of weight and lean mass loss by S‐oxprenolol was seen in the Yoshida rat model, whereas R‐oxprenolol had only had a significant effect on fat mass. S‐oxprenolol also non‐significantly reduced weight loss in the LLC model and also improved muscle function (grip strength 428 ± 25 and 539 ± 37 g/100 g body weight for placebo and S‐oxprenolol, respectively). However, there was only a minor effect on quality of life indicators food intake and spontaneous activity in the Yoshida model (25 mg/kg/S‐oxprenolol: 11.9 ± 2.5 g vs placebo: 4.9 ± 0.8 g, P = 0.013 and also vs 25 mg/kg/d R‐oxprenolol: 7.5 ± 2.6 g, P = 0.025). Both enantiomers had no effects on cardiac dimensions and function at the doses used in this study. Western blotting of proteins involved in the anabolic/catabolic homoeostasis suggest that anabolic signalling is persevered (IGF‐1 receptor, Akt) and catabolic signalling is inhibited (FXBO‐10, TRAF‐6) by S‐pindolol, but not he R‐enantiomer. Expression of glucose transporters Glut1 and Glut 4 was similar in all groups, as was AMPK. Conclusions: S‐oxprenolol is superior to R‐oxprenolol in cancer cachexia animal models and shows promise for a human application in cancer cachexia.